EL EXTRANJERO DE ELEA Y LA “SOFÍSTICA DE NOBLE LINAJE” (PLATÓN, SOFISTA 230 E5-231 B8) - Spinassi, Miguel Ángel (Exemplaria Classica, 2014)
The following paper deals with the famous passage of Sophist 230e5-231b8. My basic assumption holds that the sophist would not be the one who appears in the sixth definition as the practitioner of elenchus, but the true philosopher, represented in the dialogue by the figure of the Eleatic Stranger.